Dirty Hands and Moral Injury - Wiinikka-Lydon, Joseph (Cambridge University Press, 2018)
Moral injury describes the effects of violence on veterans beyond what trauma discourse can describe. I put moral injury in conversation with a separate but related concept, dirty hands. Focusing on Michael Walzer's framing of dirty hands and Jonathan Shay's understanding of moral injury, I argue that moral injury can be seen as part of the dirt of a political leader's dirty hands decisions. Such comparison can focus more attention on the broader institutional context in which such dirty hands decisions are executed, while contributing to the growing vocabulary of moral conflict, trauma, and harm.
Dirty Hands and Moral Injury
Keywords: moral; injury; trauma; harm; moral conflict; moral; injury; trauma; harm; moral conflict